Therapeutic Factors Affecting the Cognitive Behavioral Treatment of Bulimia Nervosa via Telemedicine versus Face-to-Face Delivery - Ertelt, Troy W. (Int J Eat Disord, 2010)
OBJECTIVE: Recently, Mitchell and colleagues (2008) conducted a randomized controlled trial of an empirically supported treatment for bulimia nervosa (BN) delivered face-to-face (FTF-CBT) or via telemedicine (TV-CBT). Results suggested that the TV-CBT and FTF-CBT were generally equivalent in effectiveness. The objective of the current study was to examine ratings of therapeutic alliance factors in TV-CBT and FTF-CBT. METHODS: Data obtained from 116 adults who met criteria for BN or eating disorder—not otherwise specified (EDNOS) with binge eating or purging weekly and 6 doctoral-level psychologists who delivered the therapy were used in the analyses. RESULTS: Therapists generally endorsed greater differences between the treatment delivery methods than patients. Patients tended to make significantly higher ratings of therapeutic factors than therapists. DISCUSSION: TV-CBT is an acceptable method for the delivery of BN treatment compared to FTF-CBT, and TV-CBT is more easily accepted as a treatment delivery method by patients than therapists.